Pengaruh Motivasi Belajar dan Kemandirian Belajar Terhadap Nilai Mid Semester Genap Tahun Ajaran 2018/2019 Pada Mata Pelajaran Komunikasi Bisnis Siswa Kelas X Jurusan Bisnis Daring dan Pemasaran SMK Negeri 3 Padang - Fatmawati Fatmawati; Z Mawardi Effendi (Universitas Negeri Padang, 2019)
The Influence of Learning Motivation and independence of Learning on the result OF Communication Business Learning Class X Business Daring and Marketing SMK Negeri 3 Padang Academic Year 2018/2019. The analytical method used is multiple regression analysis using the SPSS 25 program. This research wants understands whether there are: 1) the Influence of Learning Motivation and Independence of Learning together with the result of communication business learning Class X Business Daring and Marketing SMK Negeri 3 Padang Academic Year 2018/2019, 2) the Influence of Learning Motivation on the result of Communication Business Learning, 3) the influence of independence of Learning on the result of Communication Business Learning.Keywords: learning motivation, learning independence